(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the semantic nuances of the word “dam,” which is widely used in both Tajik and Uzbek languages. Examples from the works of great scholars are provided to illustrate each meaning. Additionally, the differences between polysemous words, monosemous words, and homonyms are discussed.